IASelect: finding best-fit agent practices in industrial CPS using graph databases - Sharma, Chandan (2020)
The ongoing fourth Industrial Revolution depends mainly on robust Industrial Cyber-Physical Systems (ICPS). ICPS includes computing (software and hardware) abilities to control complex physical processes in distributed industrial environments.Industrialagents,originatingfromthewell-established multi-agent systems ﬁeld, provide complex and cooperative control mechanisms at the software level, allowing us to develop larger and more feature-rich ICPS. The IEEE P2660.1 standardisation project, ”Recommended Practices on Industrial Agents: Integration of Software Agents and Low Level Automation Functions” focuses on identifying Industrial Agent practices that can beneﬁt ICPS systems of the future. A key problem within this project is identifying the best-ﬁt industrial agent practices for a given ICPS. This paper reports on the design and development of a tool to address this challenge. This tool, called IASelect, is built using graph databases and provides the ability to ﬂexibly and visually query a growing repository of industrial agent practices relevant to ICPS. IASelect includes a front-end that allows industry practitioners to interactively identify best-ﬁt practices without having to write manual queries.